Deteksi Konsentrasi Fe, Cu, Zn dan Pb Air Sungai dan Ikan yang Tercemar Air Lindi di Bandar Lampung Dengan Menggunakan SSA: Detections of Fe, Cu, Zn and Pb Concentration in River Water and Fish Polluted by Leachate in Bandar Lampung Using AAS - Riana, Elisa Nurma; Andriyana, Ahmad Dodi; Mulyana, Jeane Siswitasari; Khairani, Iffa Afiqa (Jurnal Sumberdaya Hayati, 2024)
Leachate is a pollutant produced by landfills which can pollute the aquatic environment. This will have an impact on fish that live in waters contaminated with leachate and if consumed by the public it will harm health. The toxic effects of leachate are caused by the content of toxic chemicals, one of which is heavy metals. The aim of this research was to determine the concentrations of Fe, Cu, Zn and Pb in Bakung landfill leachate, Sukamaju river water and fish meat. Bakung landfill leachate samples were taken from two outlet points. The fish sampling location was carried out in the Sukamaju River. The physical factors of water measured are temperature, pH, salinity, turbidity, DO, COD and BOD. Fe, Cu, Zn and Pb concentrations were measured using the Atomic Absorption Spectrophotometry (AAS) method. The results show that the physicochemical parameters in leachate and river water exceed the threshold. The contents of Zn, Cu, Fe and Pb in the leachate at both outlet points exceeded the threshold value with values of 2.48 mg/L and 2.80 mg/L; 16.55 mg/L and 17 mg/L; 0.078 mg/L and 0.113 mg/L; 3.26 mg/L and 3.01 mg/L. The concentration of heavy metals Pb and Fe in river water is 0.083-0.162 mg/L and 2.68-2.97 mg/L which are above the quality standard value, while the heavy metal Fe content in fish meat exceeds the specified threshold value, namely 0.557 mg/100 g and 0.564 mg/100 g.